∫ 0 1 x 2 − 1 ln ( x 2 ) d x = b π a
If the equation above holds true for positive integers a and b , find a × b .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
I = − ∫ 0 1 1 − x 2 ln ( x 2 ) d x = − ∫ 0 1 n = 0 ∑ ∞ x 2 n ln x 2 d x = − n = 0 ∑ ∞ ∫ 0 1 x 2 n ln x 2 d x = − n = 0 ∑ ∞ d n d ∫ 0 1 x 2 n d x = n = 0 ∑ ∞ − d n d 2 n + 1 1 = n = 0 ∑ ∞ ( 2 n + 1 ) 2 2 = n = 1 ∑ ∞ n 2 2 − n = 1 ∑ ∞ ( 2 n ) 2 2 = 6 2 π 2 − 1 2 π 2 = 4 π 2
Since the integral is from 0 to 1 , we must have x ≤ 1 . After using partial fractions, the integral splits into two integrals,each of which could be written as an infinite geometric series and which when calculated, give ζ ( 2 ) and η ( 2 ) respectively. So the answer is ζ ( 2 ) + η ( 2 ) = ζ ( 2 ) ( 1 + 1 − 2 − 1 ) = 4 π 2 . Hence answer is 2 ∗ 4 = 8
(I'm not actually showing that the two integrals obtained after using partial fractions evaluate to ζ ( 2 ) and η ( 2 ) because there are many steps involved (including LHopital's rule). But the answer was indeed having this surprisingly closed expression in terms of zeta and eta). :)
Problem Loading...
Note Loading...
Set Loading...
Rewriting using partial fractions as 2 ∫ 0 1 2 ( x − 1 ) ln x d x + 2 ( x + 1 ) − ln x d x
∫ 0 1 ( x + 1 ) ln x d x = [ ln ( x ) ln ( x + 1 ) ] 0 1 − ∫ 0 1 x ln ( x + 1 ) d x = 0 − 1 2 π 2
∫ 0 1 ( x − 1 ) ln x d x = 6 π 2 , both by expanding and integrating the power series for ln ( x ) about x = 1
6 π 2 + 1 2 π 2 = 4 π 2